Putting the Pieces Together: Using “Off-The-Shelf” Software to Safely Transfer Medical Data - Swoboda, W. J.; Göttler, M.; Zinnhobler, K.; Hasford, J. (Methods of Information in Medicine, 2001)
We describe a new computer-based, network-driven system for administering, transferring, and evaluating reports of spontaneous adverse drug reactions and serious adverse events. The system consists of three regional centers, one coordinating center, and a central database at the national drug regulatory authority. In view of its high level of data security, reliability, easy expandability, and inexpensiveness due to the use of standard shareware products, the system can serve as a model for a clinical health information network.
Keywords: Common Health Information Network (CHIN); Data Security; Digital Signature; RSA; Adverse Drug Reaction (ADR)